2020
DOI: 10.1128/aac.01652-20
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Nucleoside Analogs for Human Coronaviruses

Abstract: Coronavirus disease 2019 (COVID-19) is a serious illness caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2 or CoV-2). Some reports claimed certain nucleoside analogs to be active against CoV-2, and thus needed confirmation. Here, we evaluated a panel compounds and identified novel nucleoside analogs with antiviral activity against CoV-2 and HCoV-OC43 while ruling out others. Of significance sofosbuvir demonstrated no antiviral effect against CoV-2 and its triphosphate did not inhibit CoV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(73 citation statements)
references
References 34 publications
2
71
0
Order By: Relevance
“…This mechanism was experimentally proven by Chien et al, who demonstrated that SARS-CoV-2 RdRp can incorporate the triphosphate forms of sofosbuvir and tenofovir, thus blocking the incorporation of further nucleotide triphosphates [ 141 ]. On the other hand, the studies performed by the group of Schinazi showed no antiviral effect for sofosbuvir against SARS-CoV-2 [ 142 ]. In contrast, a randomized controlled trial on COVID-19 patients showed that adding this drug to standard care significantly reduced hospital stay duration but did not have any statistically-significant benefit on mortality [ 143 ].…”
Section: Nucleoside Analogs As Anti-hcov Drugsmentioning
confidence: 99%
“…This mechanism was experimentally proven by Chien et al, who demonstrated that SARS-CoV-2 RdRp can incorporate the triphosphate forms of sofosbuvir and tenofovir, thus blocking the incorporation of further nucleotide triphosphates [ 141 ]. On the other hand, the studies performed by the group of Schinazi showed no antiviral effect for sofosbuvir against SARS-CoV-2 [ 142 ]. In contrast, a randomized controlled trial on COVID-19 patients showed that adding this drug to standard care significantly reduced hospital stay duration but did not have any statistically-significant benefit on mortality [ 143 ].…”
Section: Nucleoside Analogs As Anti-hcov Drugsmentioning
confidence: 99%
“…In addition, it has a challenging pharmacological profile allowing intravenous administration only [39][40][41] . We demonstrate that the parent nucleoside GS-441524 [12][13][14][15][16] can "sterilize" H(s)AEC cultures from SARS-CoV2 as no rebound of the virus was noted several days after removal of the molecule. Differences in antiviral potencies of RDV and GS-441524 have been reported depending on the cell lines used, which correlates with the formation of the biologically active (5'-triphosphate) metabolite 12,13 .…”
Section: Discussionmentioning
confidence: 99%
“…Three nucleoside analogues that are known as inhibitors of SARS-CoV-2 replication were selected as reference for studies in HAEC cultures. These included GS-441524 [12][13][14][15][16] (the parent nucleoside of RDV), EIDD-1931 [16][17][18] (the active metabolite of Molnupiravir) and AT-511 17 [a guanosine nucleotide analogue with activity against hepatitis C virus (HCV)]. In order to select a suitable concentration range of these molecules to be used in the HAEC cultures, we first explored their effect in VeroE6 and Huh7 cell lines.…”
Section: Effect Of Selected Antivirals On Sars-cov-2 Replication In Hmentioning
confidence: 99%
“…Remdesivir is a nucleoside analog that acts as a small molecule inhibitor of an essential coronavirus enzyme complex, the RNA-dependent RNA polymerase (4). Nucleoside analogues are one of the largest and most effective classes of small molecule drugs against viruses like human immunodeficiency virus, hepatitis B virus and herpesviruses (5,6). The efficacy of remdesivir as a COVID-19 treatment remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Besides remdesivir, several other clinically approved nucleoside analog compounds are currently under study for treating COVID-19. Molnupiravir (11,12) and AT-527 (13) are the most promising candidates so far, while ritonavir (14), ribavirin (15), favipiravir (16) and sofosbuvir (6,17) have not demonstrated significant antiviral effect against SARS-CoV-2 in laboratory or clinical settings.…”
Section: Introductionmentioning
confidence: 99%